Plasma Neurofilament Light as a Biomarker of Neurological Involvement in Wilson's Disease. Issue 2 (20th October 2020) - Shribman, Samuel; Heller, Carolin; Burrows, Maggie; Heslegrave, Amanda; Swift, Imogen; Foiani, Martha S.; Gillett, Godfrey T.; Tsochatzis, Emmanuel A.; Rowe, James B.; Gerhard, Alex; Butler, Chris R.; Masellis, Mario; et al.
Abstract: Background: Outcomes are unpredictable for neurological presentations of Wilson's disease (WD). Dosing regimens for chelation therapy vary and monitoring depends on copper indices, which do not reflect end‐organ damage. Objective: To identify a biomarker for neurological involvement in WD. Methods: Neuronal and glial‐specific proteins were measured in plasma samples from 40 patients and 38 age‐matched controls. Patients were divided into neurological or hepatic presentations and those with recent neurological presentations or deterioration associated with non‐adherence were subcategorized as having active neurological disease. Unified WD Rating Scale scores and copper indices were recorded. Results: Unlike copper indices, neurofilament light (NfL) concentrations were higher in neurological than hepatic presentations. They were also higher in those with active neurological disease when controlling for severity and correlated with neurological examination subscores in stable patients. Conclusion: NfL is a biomarker of neurological involvement with potential use in guiding chelation therapy and clinical trials for novel treatments. © 2020 University College London. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society